Measures To Enhance Capacity Of Teachers Being Personnel – In – Charge Of The Ho Chi Minh Young Pioneer Organization ( HYPO) In Vietnam In Present Period - Dr. Long H. Nguyen , Dr.LinhN.Pham ,Dr.Thuy T.T. Le (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solutions (measures) to enhance (improve) the capacity of teachers being personnel-in-charge of the Ho Chi Minh Youth Pioneer Organization (HYPO) play an important role in enhancing (improving) the quality of the Team work and the children's movement in schools. Current reality shows that the majority of teachers being HYPO’s personnel-in-charge have a spirit of love and passion for their jobs and their pupils or students, so they engage with their work. However, because they have not been trained by a methodical and professional manner, and along with the remuneration regime, policies and job characteristics, they sometimes face many difficulties when performing their tasks. The study is conducted with a survey on 160 teachers being HYPO’s personnel-in-charge in four provinces represented for three Northern - Central – Southern regions in Vietnam. The study results show that all three groups included in the survey to improve the capacity of teachers being HYPO’s personnel-in-charge are all evaluated as effective by the targeted object groups. In which, the group of measures related to remuneration policies and regimes related to teachers being HYPO’s personnel-in-charge is the group of measures that are more effective than the other two groups of measures